Host microRNA analysis in cyprinid Herpesvirus-3 (CyHV-3) infected common carp - Michal Reichert; Anna Lukasik; Piotr Zielenkiewicz; Marek Matras; Joanna Maj-Paluch; Magdalena Stachnik; Ewa Borzym (BMC Genomics, 2019)
Abstract Background The mechanism of latency and the ability of the cyprinid herpesvirus 3 (CyHV-3) to establish life-long infections in carp remains poorly understood. To explain the role of miRNAs in this process we applied a range of molecular tools including high-throughput sequencing of RNA libraries constructed from the blood samples of infected fish followed by bioinformatic and functional analyses which show that CyHV-3 profoundly influences the expression of host miRNAs in vivo. Results We demonstrated the changed expression of 27 miRNAs in the clinical phase and 5 in the latent phase of infection. We also identified 23 novel, not previously reported sequences, from which 8 showed altered expressions in control phase, 10 in clinical phase and 5 in latent phase of infection. Conclusions The results of our analysis expand the knowledge of common carp microRNAs engaged during CyHV-3 infection and provide a useful basis for the further study of the mechanism of CyHV-3 induced pathology.